Origami-Inspired Shape Memory Folding Microactuator - Seigner, Lena; Bezsmertna, Olha; Fähler, Sebastian; Tshikwand, Georgino Kaleng; Wendler, Frank; Kohl, Manfred (The 1st International Electronic Conference on Actuator Technology: Materials, Devices and Applications), 2020)
This paper presents the design, fabrication and performance of origami-based folding microactuators based on NiTi films showing the one-way shape memory effect. Freestanding NiTi films are micromachined by laser cutting or photolithography to achieve double-beam structures allowing for direct Joule heating with an electrical current. The NiTi microactuators are interconnected to rigid sections (tiles) forming an initial planar system that self-folds into a predetermined 3D shape upon heating. A thermo-mechanical treatment is used for shape setting of as-received specimens to approach a maximum folding angle of 180°. The bending moments, bending radii and load-dependent folding angles upon Joule heating are evaluated. The shape setting process is particularly effective for small bending radii, which, however, generates residual plastic strain. After shape setting, unloaded beam structures show recoverable bending deflection between 0° and 140° for a maximum heating power of 900 mW. By introducing additional loads to account for the effect of the tiles, the smooth folding characteristic evolves into a sharp transition, whereby full deflection up to 180° is reached.<br
Keywords: self-folding origami; microactuation; shape memory alloy films; microtechnology